2022
DOI: 10.3390/ma15217512
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical Mapping of Hard Tissues by Atomic Force Microscopy: An Application to Cortical Bone

Abstract: Force mapping of biological tissues via atomic force microscopy (AFM) probes the mechanical properties of samples within a given topography, revealing the interplay between tissue organization and nanometer-level composition. Despite considerable attention to soft biological samples, constructing elasticity maps on hard tissues is not routine for standard AFM equipment due to the difficulty of interpreting nanoindentation data in light of the available models of surface deformation. To tackle this issue, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…As a result, indentation becomes an irreversible process, or, in other words, residual indent is found on the sample, and elastic–plastic deformation regime should be assumed to fit the data [ 38 ]. In our work, the usage of nanometrically sharp tips for better spatial resolution implies h ~ R , therefore the modified Hertz model of Section 2.2 can be used to fit the data [ 41 , 42 , 43 ]. This allowed to numerically process nanometric indentations into PEEK, while the usage of low-stiffness cantilevers allows investigating the polymer mechanical response to small applied forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, indentation becomes an irreversible process, or, in other words, residual indent is found on the sample, and elastic–plastic deformation regime should be assumed to fit the data [ 38 ]. In our work, the usage of nanometrically sharp tips for better spatial resolution implies h ~ R , therefore the modified Hertz model of Section 2.2 can be used to fit the data [ 41 , 42 , 43 ]. This allowed to numerically process nanometric indentations into PEEK, while the usage of low-stiffness cantilevers allows investigating the polymer mechanical response to small applied forces.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoindentations were operated on a grid pattern within 5 × 5 µm 2 large topographies of the sample, with loading–unloading curves extracted at each point of the grid. Besides E , other useful quantities derived from the curves could be mapped, such as the maximum indentation depth h max and the elasticity index, 0 < η el < 1; the latter is defined as the ratio between the areas under the unloading and loading curves and indicates the degree of elasticity of the deformation at each point of indentation [ 35 , 42 ]. We show that these three quantities, which can be obtained simultaneously from a single indentation grid, provide comprehensive characterization of the nanomechanics of PEEK and promote AFM-based nanomechanical mapping as a mean to identify and quantify the spatial localization of the moduli originated by the contributions of different surface phases of the polymer, as well as to monitor changes of such distributions due to chemical and physical modification of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…211 Atomic force microscopy (AFM), using contact or tapping modes, can be used to reveal nanoscale features (e.g., collagen fibrils and HAp crystals), while the nanoindentation mode is useful for nanomechanical modulus mapping. [229][230][231] Sub-resonance AFM (e.g., PeakForce Tapping mode) has also been developed for nanomechanical mapping 232 and was used by Zhou et al to evaluate bone tissue submerged in an aqueous environment. 233 It was also shown that micro-CT has also been coupled with mechanical testing to measure contact area and 3D full-field strain in bone/dental implant constructs; 234 such a method could likewise be highly informative to the assessment of bioactive scaffolds.…”
Section: In Vivo and Ex Vivo Methods To Assess Scaffold Bioactivitymentioning
confidence: 99%
“…As already mentioned, the equations presented in this section are valid for elastic half-spaces; however, they are extensively used when testing biological samples to create Young’s modulus maps [ 17 , 25 ]. A Young’s modulus map is created when multiple force–indentation curves are obtained on a selected region [ 26 , 27 , 28 ]. A typical illustration of the method is shown in Figure 2 c, where the selected area has been divided into 8 × 8 = 64 nanoregions.…”
Section: Elastic Half Space Assumption and Standard Young’s Modulus Mapsmentioning
confidence: 99%